Silure et PCB : deux intrus dans l’espace fluvial pour penser l’ordre naturel - Gilles Armani (Éditions en environnement VertigO, 2011)
In this contribution, our purpose is to compare two exogenous elements of the Rhone (France). After being introduced into the river environment, these elements passed to be a subject of media interest, questions, and anguish, and to a construction of an speech with similar cognitive processes. Even thought they are two very different things - a fish (wels catfish) and micro-pollution (PCBs), and are related to other issues, our approach aims to understand the construction of symbolic representations. Following interrogations that they raises, catfish and PCBs are considered as useful vectors for society analysis. Besides they reveal the concerns on the relationship of man to nature.